Urinary netrin-1 predicts early ischemic acute kidney injury after cardiopulmonary bypass - Mohammad H Aly; Alsayed Alnahal; Goerge Emad; Abdel A.M Jumaa; Mohammad M El Shaarawy (SpringerOpen, 2017)
Background Serum creatinine is an unreliable early biomarker for the diagnosis of acute kidney injury (AKI) after cardiac surgery. We need to search for a rapid and dependable marker for the detection of AKI. Aim of work This study was designed to test urinary netrin-1 (Ntn1) as a marker of early kidney injury post cardiac surgery. Our study included 39 patients with preoperative normal creatinine. We measured serum creatinine and urinary Ntn1 at 0, 6, and 24 h after cardiac surgery, AKI was defined according to the KDIGO 2012 definition. Results Fourteen patients developed AKI after cardiac surgery. There was statistically significant elevation in urinary Ntn1 at 6 and 24 h after cardiopulmonary bypass (CPB) surgery in the AKI group, while serum creatinine failed to show any statistically significant elevation at 6 h after CPB in the same group. No statistically significant change was seen in the level of creatinine or urinary Ntn1 at 6 and 24 h after CPB surgery in the non-AKI group. The sensitivity and specificity of urinary Ntn1 to detect AKI at 6 h after CPB surgery was 86.7 and 91.7%, respectively, at a cutoff value of 107.3 pg/ml. Combined urinary Ntn1 and serum creatinine had the same sensitivity and specificity. Conclusion Urinary Ntn1 may be considered as an early sensitive biomarker of AKI at 6 h after cadiopulmonary bypass surgery instead of serum creatinine that rises only 24 h after CPB surgery in patients with cardiac surgery-associated acute kidney injury.